Transformasi Digital, Big Data, dan Kinerja Keputusan: Integrasi Meta-Analisis, Systematic Review, dan Bibliometrik - Niken Saptarini; Aris Sugiarto; Sriyatun Sriyatun (LPPM Institut Pendidikan Nusantara Global, 2026)
This study conducts a comprehensive synthesis to evaluate the impact of Digital Transformation and Big Data on Business Decision Performance. Employing a mixed-methodology approach that integrates a Systematic Literature Review (SLR), bibliometric mapping, and meta-analysis, this study consolidates findings from selected literature spanning the period 2014–2024. The meta-analytic results from 40 empirical studies confirm that Big Data Analytics (BDA) capability exerts a strong and significant positive effect on Decision Quality (r = 0.52) and a moderate effect on Firm Performance (r = 0.38). Further analysis reveals that this relationship is mediated by enhanced innovation and operational agility, and moderated by environmental dynamism, wherein the value of BDA peaks in highly turbulent markets. Bibliometric mapping identifies a thematic evolution toward “Decision Intelligence” and integration with sustainability issues. The research implications underscore the need for a shift from purely technological investment toward fostering a data-driven culture, organizational dynamic capabilities, and contextual analytics strategies in order to realize optimal business value.